Use of Levosimendan in Cardiac Anesthesiology - L. A. Krichevsky; V. Yu. Rybakov; O. G. Guseva; I. E. Kharlamova; A. Yu. Lyamin (Общая реаниматология, 2011)
The authors consider the main aspects of the rational use of the novel inotropic drug levosimendan in cardiosurgical patients on the basis of the results of the trials described in the literature and on their own findings in this review. The purpose of the analysis made was to provide a rationale for the effective use of this drug. The review shows the role of the ultrasound indicator left ventricular ejection fraction, the prognostic scale EuroSCORE, and the natriuretic peptides NT-proBNP and BNP in defining indications for levosimendan administration for preoperative preparation. There are original data on the lower level of the natriuretic peptides due to levosimendan therapy. The target hemodynamic monitoring values indicating that it is essential to use levosimendan in postperfusion heart failure are discussed. It is shown that it is expedient to use levosimendan simultaneously with traditional medical measures, by taking into account the pharmacokinetic features of a calcium sensitizer. The problem of levosimendan readministration in patients operated on the heart as well is stated. That there are no clear algorithms for repeated use of the drug is shown. At the same time, possible options of this therapy in different clinical situations are given. Key words: levosimendan, cardiosurgery, heart failure.